The Role of Credit for Poverty Alleviation in Indonesia: Evidence from Panel Data Analysis - Ilyasa, Wahyu Nur; Kurniawan, Mahrus Lutfi Adi; Lubis, Firsty Ramadhona Amalia; Salim, Agus (Universitas Bangka Belitung, 2025)
The challenge of zero poverty by 2030 is difficult to achieve amidst global uncertainty which has an impact on the domestic economy through a decrease in social budgets and a decrease in purchasing power which makes the domestic economy move slowly. The Asian Development Bank (ADB) has discussed the role of banking in alleviating poverty both directly and indirectly through industrialization, MSMEs and increasing productivity which has a multiplier effect on increasing employment and reducing poverty. Challenges regarding the link between the bank and non-bank financial industry to poverty alleviation are becoming increasingly high due to increasing global uncertainty in the last decade which has had an impact on the domestic economy. This research aims to analyze the influence of banking credit (in this study using MSME credit) and People's Business Credit (KUR) as government representatives in helping business actors to improve their businesses by accessing credit with low interest on poverty alleviation in Indonesia. The research combines time series data in this study, namely the 2017-2022 period and cross section data collected from 34 provinces in Indonesia using the Panel Feasible Generalized Squared (FGLS) approach. The research results show a contradiction between people's business credit and credit to MSMEs, where people's business credit cannot alleviate poverty while credit to MSMEs is effective in reducing poverty rates. The research implication is that financial sector development can be oriented towards alleviating poverty by implementing policies that support financial system stability.